Job search behavior over the business cycle - Toshihiko Mukoyama; Christina Patterson; Ayşegül Şahin (Federal Reserve Bank of New York, 2014)
We create a novel measure of job search effort starting in 1994 by exploiting the overlap between the Current Population Survey and the American Time Use Survey. We examine the cyclical behavior of aggregate job search effort using time series and cross-state variation and find that it is countercyclical. About half of the countercyclical movement is explained by a cyclical shift in the observable characteristics of the unemployed. Individual responses to labor market conditions and drops in wealth are important in explaining the remaining variation.
Keywords: E24; E32; J22; J64; 330; job search; time; use; business cycles